Perspectives on medical education in radiation oncology and the role of the ESTRO School - Jesper Grau Eriksen; Michelle Leech; Kim Benstead; Christine Verfaillie (Clinical and Translational Radiation Oncology, 2016)
Radiation oncology is a medical specialty not just delivering ionizing radiation to cancer patients but also participating as an important partner in the care of the patient from diagnosis to cure, follow up or end of life. The specialty is rapidly evolving in a multi- and interdisciplinary setting as multimodality treatment is becoming frequent. This requires that the medical undergraduate and postgraduate training evolve to these changes. The ESTRO School has for more than 30 years offered postgraduate training courses in and outside Europe and strives to develop its services to accommodate the educational needs of a specialty in constant development. Some of these developments are described in the present paper.